From Keyboard to Heart: Maintaining Ethics in the Fast-Paced Digital Era at SMAN 6 Mataram - Ananda Kurnia Rika; Siti Nurhaliza; Nazilul Barkiah; Anggi Hermawan Saputra; Rohmat Rizwan Hidayat; Aldi Abdul Gani; Ibronayama (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Communication in this fast-paced digital era is more often done via digital platforms such as social media, instant messaging applications and other online forums. The title